2022
DOI: 10.30683/1927-7229.2022.11.03
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Investigate the Role of Noncoding RNA miR146 Alpha as a Potential Biomarker in Prostate Cancer

Abstract: There is a need for additional biomarkers for the diagnosis and prognosis of prostate cancer. MicroRNAs are a class of non-protein coding RNA molecules that are frequently dysregulated in different cancers including prostate cancer and show promise as diagnostic biomarkers and targets for therapy. Here we describe the role of micro RNA 146 a (miR-146a) which may serve as a diagnostic marker for prostate cancer, as indicated from the data presented in this report. Also, a pilot study indicated differential expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…It has also been shown that miR-146a is upregulated in PC cell lines and tissues, indicating its potential as an onco-miR [ 141 ]. MiR-15b-5p and miR-106b-5p were significantly upregulated in aggressive PC tissue and correlated with disease aggressiveness [ 142 ]. Furthermore, a prognostic score combining the levels of miR-15b-5p and miR-106b-5p with serum PSA levels discriminated between indolent PC and an aggressive form with even higher accuracy [ 143 ].…”
Section: Mirna As a Prostate Cancer Biomarkermentioning
confidence: 99%
“…It has also been shown that miR-146a is upregulated in PC cell lines and tissues, indicating its potential as an onco-miR [ 141 ]. MiR-15b-5p and miR-106b-5p were significantly upregulated in aggressive PC tissue and correlated with disease aggressiveness [ 142 ]. Furthermore, a prognostic score combining the levels of miR-15b-5p and miR-106b-5p with serum PSA levels discriminated between indolent PC and an aggressive form with even higher accuracy [ 143 ].…”
Section: Mirna As a Prostate Cancer Biomarkermentioning
confidence: 99%